O034 Incidentally enlarged iliac lymph nodes in renal transplantation – a sting in the tail!. (22nd July 2022) - Malik, AK; Moulding, S; Manas, DM; Rix, D; Sen, G; Amer, A; White, SA; Figuiereido, R; Talbot, D; Wilson, CH
Abstract: Introduction: During renal transplant, lymphadenectomy around the iliac vessels is performed to provide adequate access. Enlarged iliac lymph nodes have unclear clinical significance and standard guidance. We audited lymph node histopathology to evaluate their significance. Methods: Two audit cycles (January to August 2020 and September 2020 to October 2021, respectively) were performed. Following the first cycle, recommendation was that all enlarged lymph nodes should be biopsied. We reviewed patient histopathology and subsequent follow-up of patients with enlarged lymph nodes. Results: 241 patients underwent renal transplantation, with 19 Patients having enlarged lymph nodes (median 35mm, range 12–77mm, figure 1) sent for histopathology. Specimens from 16 patients showed benign/reactive changes (7 patients CMV positive, 14 EBV positive). Two specimens contained no lymph node. One patient (CMV and EBV positive) demonstrated evidence of chronic lymphocytic leukaemia, followed up with a bone trephine biopsy and staging CT. Staging revealed lymphadenopathy on both sides of the diaphragm and an incidental 19mm renal cell carcinoma in the native right kidney. A watch and wait strategy was employed. All 19 patients who underwent lymph node sampling were alive at last follow up. Conclusion: A literature review revealed no study into the best practice for managing incidentally enlarged lymph nodes. They are of unclear significance but may represent significant pathology requiring further follow up and management. We recommend that all lymph nodes with suspicious features and/or measuring >30mm are sampled for histopathology. Take-home message: Enlarged lymph nodes (>30mm) should be biopsied, as they may be associated with significant pathology requiring follow up and/or intervention.